Peran Guru IPS dalam Penanaman Pendidikan Karakter Peduli Sosial pada Pembelajaran di Kelas 7 SMP Negeri 2 Ciwaringin Kabupaten Cirebon - Cendanu, Citra; Bramasta, Dhi (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2023)
Character education is all efforts made by teachers to influence student character. Social awareness is defined as a pattern of behavior or readiness to adapt in social situations. This research uses a qualitative method that focuses on understanding meaning rather than generalization. In this method, researchers collect data purposively and snowball. Research Results: Teachers as educators have a responsibility to understand values, norms, morals and social aspects. The role of the teacher is also important in teaching which can shape the character of students. Teachers as models for students also have a big impact in developing their character. Teachers as individuals must be able to build social and emotional relationships with students. As for parents hindering teachers from developing social caring traits, if students remain self-centered and do not change, teachers will hold meetings with the students' parents to discuss their progress at school. Conclusion: Socially caring character includes various positive attitudes, such as politeness, compassion for others. All of these are important indicators in forming a socially caring character that can help students become good individuals and able to contribute positively to society. Teachers are an important model in developing the social care character of students who are caring, responsible and ethical towards fellow humans.